Psychological and lifestyle correlates of eating behavior and adiposity: Structural and latent profile modeling - Małgorzata Obara-Gołębiowska (PLoS ONE, 2026)
Background Psychological vulnerabilities, including early maladaptive schemas (EMS) and difficulties in emotion regulation, are associated with dysregulated eating and adiposity. However, evidence integrating these mechanisms with contextual and lifestyle factors within a single framework remains limited. This study examined an integrative model of psychological and lifestyle correlates of eating behavior and adiposity in a large adult sample. Methods A community sample of 1,500 adults (53% women; aged 18–65 years) completed validated measures of EMS, difficulties in emotion regulation, perceived stress, social support, eating behaviors, diet quality, and physical activity. Body mass index and waist circumference were assessed using standardized procedures. Structural equation modeling tested direct, indirect, and conditional associations, with multi-group analyses examining gender and age differences. Latent profile analysis identified subgroups with distinct psychological and lifestyle constellations. Results Higher EMS were associated with greater difficulties in emotion regulation. Emotion regulation difficulties were positively associated with emotional and habitual overeating (stronger among women) and showed a modest negative association with dietary restraint. Indirect effects of EMS via emotion regulation were small and limited to dietary restraint. Perceived stress did not moderate the EMS–emotion regulation association, whereas perceived social support showed a small buffering effect. Eating behaviors were associated with poorer diet quality related to higher body mass index and waist circumference, while physical activity and sedentary behavior showed independent associations with adiposity. Latent profile analysis supported a two-profile solution (higher- vs. lower-risk), characterized by distinct psychological, behavioral, and adiposity patterns. Conclusions Cognitive–emotional vulnerabilities are associated with eating dysregulation and adiposity, but emotion regulation plays a selective and modest mediating role limited to dietary restraint. Lifestyle behaviors contribute independently to adiposity alongside psychological pathways, supporting integrative, multidimensional models. Given the cross-sectional design, all findings are correlational and do not imply causality.